Impact of Foreign Ownership, Exchange Rate, and Zakat on the Performance of Sharia Commercial Banks in Indonesia - Fahmi Irfan (Journal of Islamic Economics Lariba, 2019)
The main objective of this study is to examine the variables that can affect the performance of Islamic Commercial Banks. Banks are required to choose management plans that can minimize the required costs and maximize the generated profits. The variables under consideration are foreign ownership, changes in the exchange rate of the Indonesian Rupiah against the US Dollar, and corporate zakat expenditure, which will be tested for their impact on the level of profitability (ROA) and efficiency (BOPO) of Indonesian Islamic Commercial Banks. This study uses panel secondary data and a purposive sampling method, which includes eleven Islamic Commercial Banks in Indonesia from 2011 to 2014. The analysis method used is multiple linear regression. The results of this study conclude that the research model simultaneously affects the ROA and BOPO of the bank. Partially, foreign ownership has a negative impact on the ROA and BOPO of the bank. Changes in the appreciation/depreciation of the Rupiah-US Dollar have a negative impact on the ROA of the bank but a positive impact on the BOPO of the bank. In addition, corporate zakat expenditure has a positive impact on the ROA of the bank, but it has no effect on the BOPO of the bank.